The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4236/ojog.2015.56053
|View full text |Cite
|
Sign up to set email alerts
|

Maternal PAPP-A Levels at 11 - 13 Weeks of Gestation Predict Foetal and Neonatal Growth

Abstract: Recent reports suggest that maternal serum levels of pregnancy-associated plasma protein A (PAPP-A) may predict perinatal outcome. PAPP-A is a syncytiotrophoblast derived protease for insulin-like growth factor binding protein (IGFBP4); its protease activity cleaves complexed growth factor binding protein increasing insulin-like growth factor I (IGF-I) bioavailability. The aim of our study was to evaluate the correlation between maternal PAPP-A serum levels and neonatal growth. We analysed 100 full term and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…This show that the birth weight, APGAR scores at 1 minute and at 5 minutes of the babies was not totally influenced by the circulating levels of the maternal AFP and PAPP-A. This was in contrast with the previous reports (Gentile et al, 2015). PAPP-A is a protease of IGFBP4 which acts as a binding protein for IGF-1 and a powerful inhibitor for IGF-1.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This show that the birth weight, APGAR scores at 1 minute and at 5 minutes of the babies was not totally influenced by the circulating levels of the maternal AFP and PAPP-A. This was in contrast with the previous reports (Gentile et al, 2015). PAPP-A is a protease of IGFBP4 which acts as a binding protein for IGF-1 and a powerful inhibitor for IGF-1.…”
Section: Discussioncontrasting
confidence: 72%
“…PAPP-A is a protease of IGFBP4 which acts as a binding protein for IGF-1 and a powerful inhibitor for IGF-1. IGF-1 plays an important role in regulating fetal growth by controlling glucose and amino acids absorption in trophoblastic cells (Gentile et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies (16, 2228) have found positive associations between early PAPP-A and the baby’s birth weight, although this finding is not universal. (18, 29) Indeed we failed to find an association when analysing raw or minimally adjusted data.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that PAPPA is a biomarker that is decreased in the serum of women who present with FGR in the first trimester ( 15 , 16 ). Giudice et al have demonstrated that neonatal weights are associated with serum PAPPA levels lower than the 25th centile ( 17 ).…”
Section: Discussionmentioning
confidence: 99%